Anesthesia- patient’s apprehension, concerns, and counseling - Dr. Chandra Shekhar Mishra; Dr. Sushant Saxena; Dr. Anuj Dubey (International Journal of Medical Research and Review, 2020)
Introduction: To allay anxiety and resolve the patient’s apprehension regarding general anesthesia through counseling. Patients presenting to PAC were asked to participate in a 2-way conversation meant to evaluate and study his apprehension, concerns in relation to anesthesia, and subsequently, a counseling session was given to answer his doubts and resolve his fear. Material and Methods: In the study, it was found the fear of death was the greatest concern. The other major concerns were fear of paralysis and heart attack. Results: The level of fear decreased as the severity of surgery decreased. For major surgery, the fear of death differed significantly with age, especially with increasing age came a lessened fear of death. Counseling by anesthesia provider regarding the fear that the patient reported help to reduce the anxiety. It allows for a more personalized approach towards the patient. It helps anesthesia provider to tailor the informed consent process. Conclusion: In general, the study increases awareness regarding anesthesia among patient and their relatives.